2015
DOI: 10.1007/s11103-015-0312-3
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic branched-chain aminotransferases of Arabidopsis thaliana influence methionine supply, salvage and glucosinolate metabolism

Abstract: Arabidopsis thaliana possesses six branched-chain aminotransferases (BCAT1-6). Previous studies revealed that some members of this protein family are involved in the biosynthesis of branched-chain amino acids and/or in the Met chain elongation pathway, the initial steps towards the biosynthesis of Met-derived glucosinolates. We now analyzed branched-chain aminotransferase 6 (BCAT6). In vivo GFP-tagging experiments strongly suggest this enzyme to be localized to the cytosol. Substrate specificity assays perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Another QTL, identified for the response to P. rapae, contained, as most likely candidates, BCAT-1 and BCAT-2, which are enzymes involved in branched amino acid (leucine (Leu), valine (Val) and isoleucine (Ile)) (BCAA) metabolism (Diebold et al, 2002). Interestingly, homologues of these genes (BCAT-3, BCAT-4, BCAT-6) have been implicated in the production of aliphatic glucosinolates (Schuster et al, 2006;Lachler et al, 2015). Furthermore, co-expression networks have revealed that BCAT-4 is co-expressed with MYB29, MYB28 and several putative genes involved in Leu metabolism (Hirai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another QTL, identified for the response to P. rapae, contained, as most likely candidates, BCAT-1 and BCAT-2, which are enzymes involved in branched amino acid (leucine (Leu), valine (Val) and isoleucine (Ile)) (BCAA) metabolism (Diebold et al, 2002). Interestingly, homologues of these genes (BCAT-3, BCAT-4, BCAT-6) have been implicated in the production of aliphatic glucosinolates (Schuster et al, 2006;Lachler et al, 2015). Furthermore, co-expression networks have revealed that BCAT-4 is co-expressed with MYB29, MYB28 and several putative genes involved in Leu metabolism (Hirai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Valine, leucine and isoleucine are called branched-chain amino acids (BCAAs), characterized by their small branched hydrocarbon residues. The breakdown or synthesis of BCAAs depends on the catalysis of the family of branched-chain aminotransferases (BCATs) (Lachler, Imhof, Reichelt, Gershenzon & Binder, 2015). BCATs catalyse the crucial step in BCAAs metabolism, a reversible transamination from BCAAs and a-ketoglutarate to corresponding branched-acid a-keto acids and glutamate (Brosnan & Brosnan, 2006).…”
Section: Enzymes Involved In Amino Acids Metabolismmentioning
confidence: 99%
“…Elbtalaue, but also identified additional aliphatic and indole glucosinolates at lower concentrations. By making use of the known glucosinolate biosynthetic genes from Arabidopsis (Hull et al 2000, Mikkelsen et al 2000, Kliebenstein et al 2001b, Kroymann et al 2001, Reintanz et al 2001, Chen et al 2003, Kroymann et al 2003, Grubb et al 2004, Mikkelsen et al 2004, Piotrowski et al 2004, Textor et al 2004, Nozawa et al 2005, Klein et al 2006, Schuster et al 2006, Hansen et al 2007, Textor et al 2007, Knill et al 2008, Li et al 2008, Farquharson 2009, Geu-Flores et al 2009, Gigolashvili et al 2009, He et al 2009, Klein and Papenbrock 2009, Knill et al 2009, Pfalz et al 2009, Sawada et al 2009, He et al 2010, Geu-Flores et al 2011, He et al 2011, Pfalz et al 2011, Lachler et al 2015, Kong et al 2016, Pfalz et al 2016,…”
Section: Glucosinolate and Myrosinase Genes In The E Cheiranthoides mentioning
confidence: 99%